Efficient synthesis of phosphorus-promoted and alkali-modified ZSM-5 catalyst for catalytic dehydration of lactic acid to acrylic acid - Ainur Syeitkhajy; Mohammed Alfatih Hamid; Mehtap Safak Boroglu; Ismail Boz (Results in Chemistry)
This study presents a novel one-pot synthesis method for phosphorus-enhanced ZSM-5 zeolite, followed by post-synthesis alkali treatment. The resulting catalyst is designed for the sustainable production of acrylic acid (AA) from lactic acid (LA). Adding phosphorus as a promoter during synthesis significantly improved the acid-base properties of the zeolite. Additionally, the alkali treatment contributed to the overall optimization of the catalyst’s performance. Comprehensive analytical techniques, including XRD, BET, FT-IR, TGA, XPS, SEM, ICP-MS, DRIFT spectra, NH3, and CO2-TPD, were employed to elucidate the structural and acid-base properties of the ZSM-5/P-Na catalyst. Finally, an experimental design was developed to optimize the important operational variables in the LA dehydration reaction. The optimized ZSM-5/P-Na catalyst demonstrated excellent performance, achieving 83 % AA selectivity and 98 % LA conversion with a long catalytic lifetime of 50 h. This research demonstrates a promising approach for developing efficient catalysts for sustainable AA production.